The Study on Water Distribution in Inceptisol Soil Planted with Soybean at Different Amount of Given Water - Juni Artina Alberta; Sumono Sumono; Adian Rindang (Jurnal Rekayasa Pangan dan Pertanian, 2016)
Knowing water distribution in soil is important as one of the reason for irrigation. This research was purposed to study water distribution in Inceptisol soil planted with soybean at 100%, 80%, 60% field capacity and its effect on soybean plant’s production. The parameters observed were the characteristic of the soil physics, field capacity, evapotranspiration, water distribution, dry weight of soybean plant and pods weight.The results showed that Inceptisol soil had sandy clay loam texture. The highest porosity was found at 6-10 cm depth i.e. 63,06%. The lowest porosity was found at 0-5cm depth i.e. 54,23%. Water field capacity was 47,7%(dry basis). Soybean plant evapotranspiration at middle growth phase was 1,97 mm/day and the last growth phase was 1,58 mm/day. The highest water level was found at 6-10 cm depth i.e. 20,58-32,49% (dry basis). The lowest water level was found at  0-5 cm depth i.e. 20,34-26,63% (dry basis). The dry weight of soybean plant at the middle growth phase at 100% field capacity was 16,51 g, at the last growth phase was 14,89 g and pods weight was 13,20 g. The dry weight of soybean plant at the middle growth phase at 80% field capacity was 14,23 g, at the last growth phase was 11,77g and pods weight was 10,78 g. The dry weight of soybean plant at the middle growth phase at 60% field capacity was 13,12 g, at the last growth phase was 10,97 g and pods weight was 8,76g. Keywords: Evapotranspiration, Field Capacity, Inceptisol Soil, Soybean Plant, Water Distribution